Proceedings of the 13th International Conference on Principles and Practices of Programming on the Java Platform: Virtual Machi 2016
DOI: 10.1145/2972206.2972221
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Program-Specific Phase Change Detection for Java Programs

Abstract: It is well-known that programs tend to have multiple phases in their execution. Because phases have impact on micro-architectural features such as caches and branch predictors, they are relevant to program performance Xian et al. [2007], Roh et al. [2009], Gu and Verbrugge [2008] and energy consumption. They are also relevant to detecting whether a program is executing as expected or is encountering unusual or exceptional conditions, a software engineering and program monitoring concern Peleg and Mendelson [20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Chiu et al [25] found that they could use variable-length intervals to improve classification accuracy. The authors proposed a technique that first traced an application's ex- Instruction type vector [86]; conditional branch execution [88]; task execution metrics frequency [41]…”
Section: Serial Online Phase Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Chiu et al [25] found that they could use variable-length intervals to improve classification accuracy. The authors proposed a technique that first traced an application's ex- Instruction type vector [86]; conditional branch execution [88]; task execution metrics frequency [41]…”
Section: Serial Online Phase Classificationmentioning
confidence: 99%
“…Variable length intervals [75] [48] [25] [108], on the other hand, allow the intervals to closely match the periodicity of the different phases and enable more accurate phase classification. However, variable length intervals are more complex, since they may require more detailed application analysis at design time or an online algorithm with a feedback loop for runtime phase classification [44].…”
Section: Intervalsmentioning
confidence: 99%
See 2 more Smart Citations